Evaluation strategies in active learning in higher education in health: integrative review - Monike Alves Lemes; Maria José Sanches Marin; Carlos Alberto Lazarini; Silvia Cristina Mangini Bocchi; Elza de Fátima Ribeiro Higa
ABSTRACT Objectives: to analyze scientific evidence on evaluation strategies for active learning methods in health undergraduate programs. Methods: integrative literature review in the Medical Literature Analysis and Retrieval System Online, Latin American and Caribbean Literature in Health Sciences, Nursing Database, Scopus, Web of Science and Education Resources Information Center databases. Results: different evaluation strategies are used: Presentation of seminars, Self-evaluation, Evaluation of student performance in Tutotest-Lite tutoring, Peer Evaluation, Active Learning and Critical Thinking Self-evaluation Scale, Objective and Structured Clinical Exam, Portfolio, Progressive Disclosure Questions, Modified Dissertation Questions, Progression Test, Dissertation Test, Objective Test, Immediate Learning Checks, Clinical Case Resolution and Cumulative Test. Final Considerations: evaluation strategies in active learning are used in combination, aiming at the affective, cognitive and psychomotor development of the student. However, studies with greater power of scientific evidence would be needed.